2011
DOI: 10.1002/ana.22345
|View full text |Cite
|
Sign up to set email alerts
|

Can semiology predict psychogenic nonepileptic seizures? a prospective study

Abstract: We identified 6 semiological signs that reliably distinguish PNES and ES, and found that eyewitness reports of these signs are unreliable. We offer suggestions to improve the accuracy of eyewitness reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
177
3
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(198 citation statements)
references
References 18 publications
12
177
3
6
Order By: Relevance
“…16 In PNES, the eyes are also usually closed during apparent TLOC. [16][17][18] Besides eye closure, the distinction from VVS can also be made by measuring the duration of the apparent TLOC, which is longer in PPS. In our series, patients with syncope never remained unresponsive for more than 1 minute, whereas PPS could last up to 14 minutes.…”
mentioning
confidence: 99%
“…16 In PNES, the eyes are also usually closed during apparent TLOC. [16][17][18] Besides eye closure, the distinction from VVS can also be made by measuring the duration of the apparent TLOC, which is longer in PPS. In our series, patients with syncope never remained unresponsive for more than 1 minute, whereas PPS could last up to 14 minutes.…”
mentioning
confidence: 99%
“…Farkındalığın korunması, göz kırpıştırma ve nöbet şiddetinin seyirci tarafından etkilenebilir olması NEPN lehine; ani başlangıç, nöbet başlangıcında gözlerde açılma-genişleme, postiktal konfüzyon ve uyku ise epileptik nöbetler lehine en güçlü semiyolojik bulgular olarak belirtilmiştir. [10] İndüksiyon ile NEPN izlenen 39 hastamızın 25'inde enjeksiyon sonrası telkinle nöbetin şiddetinin arttığı, 15 hastada ise nöbetin sadece telkinle sonuçlandığı dikkat çekmiştir. Ayrıca 27 hastanın nöbet sırasında gözlerinin kapalı olduğu, 20 hastanın nöbet sırasında yanıtsız olduğu ve 19 hastada cevaplılığın korunduğu izlendi.…”
Section: Discussionunclassified
“…Likewise, semiotics also can be used as a screening tool. Studies have shown that semiological differences between PNES and ES are reliable when performed by experts but, unfortunately, they are not as reliable, when obtained from relatives and lay persons [9].…”
Section: Diagnosismentioning
confidence: 99%